From Online to Offline and Vice Versa: Change in Internet Use in Later Life Across Europe - König, Ronny; Seifert, Alexander (Frontiers in Sociology, 2020)
The internet can be a valuable source of social participation in modern society. Although increasing numbers of older adults are using the internet, numerous older adults also cease using the internet and become “offliners.” The question of which factors in usage change (i.e., switching from onliner to offliner, and vice versa) are most influential remains unclear. This study investigates changes in internet use among the older European population using two waves of representative panel data for 13 countries from the Survey of Health, Aging and Retirement in Europe (SHARE). The analyses were based on 34,149 respondents aged 50 years and older. In general, the results indicate a positive trend by a slight (2%) increase in usage, from 51% in 2013 to 53% in 2015. However, the results also show that a total of 6% had not recently used the internet, although they had done so in the past. Our multilevel results suggest that both the onset of and cessation of internet usage are primarily driven by changes in socioeconomic resources (income and occupation), health resources (subjective health and grip strength), living situation (via relocation), and social factors (partnership and distance to children) as well as contextual factors such as country-specific wealth and social indexes and internet infrastructure. The study underlines the importance of investigating the influencing factors for commencing internet usage and of determining which factors lead to its increase.